Fabrication of In2O3/ZnO hetero-epitaxial-junctions with enhanced PEC performances. (December 2017) - Zhang, Bo; Wang, Zeyan; Zhang, Xiaoyang; Qin, Xiaoyan; Wang, Peng; Liu, Yuanyuan; Li, Mengmeng; Dai, Ying; Li, Yingjie; Huang, Baibiao
Abstract: In2 O3 /ZnO hetero-epitaxial-junction photoanodes were successfully synthesized and applied for the photoelectrochemical splitting of water. With the assistance of In2 O3, the light absorption of In2 O3 /ZnO heterojunctions can effectively expand to visible light absorption region. Due to the epitaxial relationship between (10-10) ZnO and -211 In2 O3 planes, the staggered band alignments between In2 O3 and ZnO can produce a built in electric field at the heterojunction interface with a high quality, which can promote the charge separation and lower the charge recombination under light irradiation. Moreover, low index crystal facets, such as 001 and 111 facets, with lower surface energies can be formed spontaneously in In2 O3 nanoparticles due to the surface energy conservation. And the presence of In2 O3 001 facets can effectively lower the onset potential and facilitate the water oxidation. With the synergistic effects mentioned above, In2 O3 /ZnO-6 exhibit highest photocurrent density of 2.2 mA cm −2 at 0.6 V vs Ag/AgCl and IPCE value of 88.62% at 0.25 V vs Ag/AgCl (370 nm), which is 2.82 and 4.4 times as high as that of ZnO NRs and In2 O3 photoanodes, respectively. Highlights: In2 O3 /ZnO hetero-epitaxial-junction photoanodes were successfully synthesized. Staggered band alignment of heterojunction facilitate the charge separation. The epitaxial relationship between 100 ZnO and -211 In2 O3 planes. The In2 O3 100 facets lower the overpotential for O2 evolution. The In2 O3 /ZnO photoelectrode exhibits visible light photoresponse.